Altered Intrinsic Brain Activity and Functional Connectivity Before and After Knee Arthroplasty in the Elderly: A Resting-State fMRI Study - Lan, Fei; Lin, Guanwen; Cao, Guanglei; Li, Zheng; Ma, Daqing; Liu, Fangyan; Duan, Mei; Fu, Huiqun; Xiao, Wei; Qi, Zhigang; Wang, Tianlong (Frontiers in Neurology, 2020)
Objective: This study aimed to investigate the brain functional alterations with resting-state functional magnetic resonance imaging (rs-fMRI) in older patients with knee osteoarthritis (KOA) before and after total knee arthroplasty (TKA) and to assess the causal relationship of the brain function and neuropsychological changes. Methods: We performed rs-fMRI to investigate brain function of 23 patients aged ≥65 with KOA and 23 healthy matched controls. Of the KOA patients, 15 completed postoperative rs-fMRI examinations. Analyzes of the amplitude of low-frequency fluctuation (ALFF) and functional connectivity (FC) were used to estimate differences in brain functional parameters between KOA patients, postoperative patients, and the controls. The relationship between changes of pre-and post-surgical status in ALFF and neuropsychological test results was analyzed. Results: Compared with the controls, all patients with KOA exhibited decreased ALFF in the default mode network (bilateral angular gyrus, precuneus gyrus, medial superior frontal gyrus) and increased ALFF in the bilateral amygdala and cerebellum posterior lobe before surgery (P<0.001). Altered ALFF persisted in the same brain regions one week postoperatively. The decreased ALFF in the left precuneus gyrus and middle temporal gyrus was found after surgery when compared with preoperative data (P<0.01). Preoperatively, the KOA patients exhibited increased FC between the left precuneus gyrus and the right supplementary motor area compared to the controls (P<0.01), but this connectivity was turned to no significant difference after TKA. The left Cerebelum_9 was found to have decreased FC with the right precuneus gyrus postoperatively (P<0.01), although this was not significantly different before surgery. The significantly altered ALFF values were not correlated with changes in cognitive assessment scores. Conclusion: In older patients with end-stage KOA, functional alterations in important brain regions were detected, with the persistence and further changes observed at early stage after knee replacement. Our data further our understanding of brain functional abnormalities and cognitive impairment in older patients following knee replacement which may provide therapeutic targets for preventive/treatment strategy to be developed.